ANALISA PENGARUH MARKET ORIENTATION TERHADAP PURCAHASE INTENTION DENGAN BRAND IMAGE DAN BRAND PERFORMANCE SEBAGAI VARIABEL INTERVENING PADA PT VISTA INTERNATIONAL CORPORATION - Jimmy Christian Limanto (Jurnal Strategi Pemasaran, 2015)
Competition in the educational institutions, consultation and preparation abroad is increasing, especially in a city that has a high priority to education, Surabaya.This study aimed to analyze the effects of Market Orientation on Purchase Intention with see the effect of Brand Image and Brand Performance.This study will be conducted by distributing questionnaires to 100 respondents potential customers PT VIC (Vista International Corporation). Analysis technique used is quantitative analysis techniques.